An Improved Resource Query and Location Algorithm Based on Cloud Computing - Wuxue Jiang; Jing Zhang; Junhuai Li; Hui Hu (Institute of Advanced Engineering and Science, 2013)
With the continuous development of cloud computing applications, the problems of cloud computing are more and more obvious, such as the lower efficiency of resource search, the lack of network scalability, and some difficulties in management. In this paper, the problems of P2P network and the structural characteristics of the IS-P2P network are studied. On the basis of traditional Chord algorithm, the improvement of the speed of search is made. BiChord: a resource locator and query algorithm based on cloud computing is put forward. The bidirectional routing tables FingerTable and RefingerTable are designed by this algorithm, which adopts the query strategy of bidirectional location of keywords. In addition, the paper also proposes XP query: a message query mechanism based on the structure of the cloud computing. Simulation results show that BiChord has better routing performance than traditional Chord algorithm and the message query mechanism also improves the efficiency of resource queries. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3356